THE Epidemology of down’s syndrome among congential heart disease children in Faisalabad: Epidemology of down’s syndrome among congential heart disease children in Faisalabad (European journal of volunteering and community-based projects, 2021)
Patients with Down’s syndrome are prone to have congenital heart defects. This study was conducted to evaluate the frequency of various congenital heart defects in children with Down’s syndrome. The data was collected from the Department of Cardiology in FIC (Faisalabad Institute of Cardiology) Hospital. Fifty-eight phenotypically Down syndrome children coming to the cardiology department for echocardiography, from birth to 13 years were included in this study. After detailed history and physical examination, all these patients were subjected to 2-dimentional echocardiography in addition to routine laboratory investigations. Congenital heart defects were found in 29 out of 58 patients (50%). Among the affected patients, 16 (55.2%) were males and 13 (44.8%) females with male to female ratio of 1.2:1. Acynotic lesions were more common (79.31%) than cyanotic lesion (20.69%). Among the isolated lesions ventricular septal defect, patent ductus arteriosus and complete atrioventricular defects were the commonest defects (20.69%) each, followed by pulmonary atresia (6.89%), atrial septal defect, tetralogy of Fallot, transposition of great arteries and double outlet right ventricle with ventricular septal defect (3.45%) each. Among the mixed lesions ventricular septal defect with atrial septal defect (VSD+ASD) was most common (6.89%), followed by patent ductus arteriosus with coarctation of aorta (PDA+CoA), univentricle with atrial septal defect (univentricle+ASD), and double outlet right ventricle with ventricular septal defect, patent ductus arteriosus and pulmonary atresia (DORV+VSD+PDA+pulmonary atresia) (3.45%) each. Congenital heart defects are found in 50% children with Down syndrome. The commonest are ventricular septal defect, patent ductus arteriosus and complete atrioventricular septal defect in our set-up. All children with Down syndrome should have a cardiac evaluation at birth. Down syndrome, Congenital heart disease, Transposition of great arteries, Pulmonary atresia, Tetralogy of Fallot, Ventricular septal defect.